Pengaruh Model Pembelajaran Kooperatif Tipe Problem Posing terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas XI SMAN 1 Siborongborong Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine the positive and significant influence of the Problem Posing cooperative learning model on active learning in Christian Religious Education for class XI students at SMAN 1 Siborongborong for the 2023/2024 academic year. The research method used is a quantitative method with inferential statistics. The population is all class students. Data was collected using a positive closed questionnaire with 38 items, namely 20 items for the 2023/2024 school year variables, proven through data analysis as follows: 1) Test the analysis requirements: a) Positive relationship test obtained with rxy = 0.529 > rtable (α=0.05; CI=95%; n=63) = 0.24. b) the significant relationship test obtained tcount = 4.865 > ttable(α=0.05, dk=n-2=61) = 1.9996. 2) Influence test: a) regression equation test, obtained the regression equation Y ̂="26.24"+0.46X. b) regression coefficient of determination test (r2) = 27.9%. 3) hypothesis testing using the F test obtained Fcount > Ftable (α=0.05, dk numerator k-28, dk denominator=n-2=63-2=61) namely 23.73 > 1.66. Thus Ha is accepted and H0 is rejected.